The Influence of Leadership Models, Organizational Culture, and Work Environment on Teacher Performance Moderated by Locus of Control in the New Habit Era - Achmadi Ramadhani; Nurul Badriyah; Evi Fitrotun (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
This study aims to analyze the influence of leadership models, organizational culture, and work environment on teacher performance, as well as examine the role of locus of control moderation in these relationships in the era of new habits after the Covid-19 pandemic. The research was conducted at SMAN 1 Babat Lamongan by involving 96 teachers as respondents. The method used is a quantitative approach with Partial Least Square (PLS) analysis using SmartPLS. The results showed that the leadership model had a positive and significant effect on teacher performance (T-Statistic = 3.384; p = 0.001), as well as organizational culture (T-Statistic = 3.371; p = 0.001) and work environment (T-Statistic = 2.101; p = 0.036). The locus of control was also shown to have a significant effect directly on teacher performance (T-Statistic = 2.877; p = 0.004). However, the results of the moderation test showed that the locus of control did not moderate the relationship between leadership models, organizational culture, and work environment on teacher performance. The R-Square value of 0.926 indicates that independent variables explain 92.6% of the variation in teacher performance. These findings provide practical implications for school management to strengthen leadership, develop a positive organizational culture, and improve the quality of the work environment to encourage optimal teacher performance.